Māori Linked Administrative Data: Te Hao Nui - A novel Indigenous Data Infrastructure and Longitudinal Study - Theodore, Reremoana; Boulton, Amohia; Sporle, Andrew (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2023)
Worldwide, large amounts of administrative data are collected within official statistics systems on Indigenous Peoples. These data are primarily used for government and state policy purposes as opposed to by Indigenous Peoples to support Indigenous agendas (Taylor & Kukutai, 2017). In Aotearoa me Te Waipounamu New Zealand, Māori need high quality data to develop evidence-based policies and programs and to monitor government policies that impact on Māori. In this methodological paper, we describe uses of administrative data for Māori and current barriers to its use. We outline the development of a novel administrative data infrastructure and future longitudinal study. By explicating our Indigenous initiated, designed and controlled data project, we make a methodological contribution to Indigenous Data Sovereignty and Kaupapa Māori (Māori worldview) epidemiology.